2015
DOI: 10.1002/srin.201500129
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Hardening Behavior of 18CrNiMo7‐6 via Cu Alloying

Abstract: In order to improve the rolling contact fatigue (RCF) behavior of gear steels, a concept to increase their damage tolerance is developed alternatively to the conventional approach of improving the degree of steel cleanliness. For that purpose, Cu is used as a main alloying element in order to trigger the precipitation of nano‐sized Cu precipitates which shall improve the strain‐hardening rate of the martensitic matrix of Cu‐alloyed 18CrNiMo7‐6 steel surrounding a non‐metallic inclusion during plastic deformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…This confirms that the hardening-exponent CHT (e II ) obtained from PHYBAL CHT can be compared with the cyclic hardening behavior of materials in uniaxial fatigue loading conditions [12]. Further studies by Bambach et al [14] have demonstrated a successful application of the PHYBAL CHT (e.g., to determine optimized heat treatment conditions of high strength steel for maximum damage tolerance during fatigue loadings). The present paper, however, focuses on understanding the local microstructural changes during cyclic indentation with help of MD simulations.…”
Section: Materials and Experimental Methodssupporting
confidence: 61%
“…This confirms that the hardening-exponent CHT (e II ) obtained from PHYBAL CHT can be compared with the cyclic hardening behavior of materials in uniaxial fatigue loading conditions [12]. Further studies by Bambach et al [14] have demonstrated a successful application of the PHYBAL CHT (e.g., to determine optimized heat treatment conditions of high strength steel for maximum damage tolerance during fatigue loadings). The present paper, however, focuses on understanding the local microstructural changes during cyclic indentation with help of MD simulations.…”
Section: Materials and Experimental Methodssupporting
confidence: 61%
“…The low strength zones were assumed to be a result of the scatter of carbon content in the solidified structure. 4) Metallographic characterization of non-metallic inclusions is a powerful tool to describe the steel quality. However, information on oxygen level in the melt and the NMI distribution and sizes in the solidified steel is not sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of inclusions on the mechanical behaviorespecially the fatigue behavior -was investigated as well. [4] The mechanical behavior of metallic materials is highly controlled by non-metallic inclusions in different ways. Non-metallic inclusions in solid steel act as stress raisers and promote fracture during quasi-static, dynamic, or cyclic loading.…”
Section: Introductionmentioning
confidence: 99%
“…SANS is a well-established, non-destructive method to obtain structural information about the arrangement of atoms and magnetic moments on a mesoscopic scale, from near atomic (nanometer) to near optical (micrometer) sizes, in condensed matter systems and materials from a wide range of applications. Such arrangements may be macromolecules [20], self-assembled polymeric systems [21], biomolecular aggregates [22], precipitates and SRO in metallurgical materials [23,24] or porosities in geological and construction materials [25]. Neutrons interact with matter via short-range nuclear interactions and, thus, detect the nuclei in a sample rather than the diffuse electron cloud observed by X-rays.…”
Section: Methodsmentioning
confidence: 99%